Additive Particles in Romance and Germanic Languages: Are They Really Similar? - Benazzo, Sandra; Dimroth, Christine (Linguistik Online, 2015)
The starting point of this paper is the observation of an unequal frequency of the additive particle auch in German as compared to the paucity of its French counterpart aussi, in L1 and L2 developmental data as well as in adult native speakers' production, which leads to an investigation of the reasons for the observed difference in language use. The paper brings together findings on the structure and discourse integration of utterances containing additive particles (translation equivalents of also) in written sources from French and German and in oral production data from speakers of French and Italian, German and Dutch. Next to data from native speakers, developmental data from learners of French and German (as L1 and L2) are shown to be relevant sources of information about the integration of the optional particles into utterances and at the discourse level. The developmental data reveal a difference between Romance and Germanic languages, concerning not only the frequency of additive particles, but also their interaction with early markers of assertion: auch/ook function as precursors of the assertive value, in competition with the expression of assertion through finiteness, whereas no such interaction is attested for aussi/anche. A comparison of native speakers' preferential choices concerning the information unit highlighted to enhance discourse cohesion confirms the differences between the two language families: speakers of Germanic languages preferentially use particles and Verum Focus, i. e. anaphoric links operating on the assertion value of the relevant utterances, whereas speakers of Romance languages choose anaphoric links operating on the utterance's descriptive content (entities and predicate). Although additive particles across languages share a similar basic meaning, only the Germanic ones are integrated in a system of assertion-related items that push their speakers to apply a discourse perspective oriented towards a comparison of assertions.